Properties of Spray-dried Rice Starch Microcapsule - Vipa Surojanametakul; Patcharee Tungtrakul; Warunee Varannanond; Rasamee Supasri; Smittra Boonbumroung; Kitsana Themtakul (Agriculture and Natural Resources, 2005)
This research was conducted to produce rice starch microcapsules from regular rice starches (22-24% solid w/w) with the small amount of each suitable binding agent (0.10-0.30%): acacia, carboxymetylcellulose and gelatin by using spray dryer. Scanning electron microscope (SEM) was used to examine the surface microstructure of the microcapsules. The results revealed that 24% rice starch with 0.30% either carboxymetylcellulose (CMC) or acacia and 22% rice starch with 0.30% gelatin exhibited numerous good appearances of the spherical aggregates. These selected conditions were repeated with glutinous rice starch instead of the regular one. Chemical and physical properties of all products were also investigated, most of which showed a spherical shape under SEM. Concentrations and types of the mixture between starches and binding agents did affect sizes, number and properties of the sphere starch aggregates. The spherical starch aggregates with CMC had a relatively larger in size and number than those with acacia and gelatin. The average sphere diameter of rice starch microcapsules ranged from 15.37-30.19 μm, the particle density was about 1.49-1.55 g/cm3 and the bulk density was 0.54-0.58 g/cm3. Flow characteristics of all products showed easy -to-free flowing powder types. The products possessed moisture content less than 10%, water activity (Aw) 0.20-0.41 and water absorption index (WAI) 0.28-0.70. All samples exhibited hygroscopic properties. Among the samples microcapsule with the best physical properties was made from 24% rice starch with 0.30% CMC. However, the rice starch microcapsules especially with 0.30% acacia possessed higher bulk porosity than the others and gave slightly different pasting properties from the native rice starch.